The Effect of Teacher Creativity on the Learning Motivation of Public Elementary School Students in Tomohon City - Margareta Oktavia Sumilat; Joulanda A.M. Rawis; Jeffry S.J. Lengkong; Orbanus Naharia (Peneliti.net, 2026)
This study aims to analyze the effect of teacher creativity on the learning motivation of public elementary school students in Tomohon City by using Structural Equation Modeling (SEM). This research employed a quantitative explanatory approach. The population consisted of all fifth- and sixth-grade students from 21 public elementary schools in Tomohon City. The sample size was determined using the Lemeshow formula at a 95% confidence level, resulting in 384 respondents. Data were collected through a Likert-scale questionnaire consisting of 8 indicators of teacher creativity and 10 indicators of learning motivation. Data analysis was carried out using AMOS through descriptive analysis, measurement model testing, and structural model testing. The findings revealed that teacher creativity was in the very high category with a mean score of 4.444, while students’ learning motivation was also in the very high category with a mean score of 4.392. The SEM results indicated that the proposed model had a good level of fit. Furthermore, teacher creativity had a positive and significant effect on students’ learning motivation, with a standardized path coefficient of 0.471 and a significance value of p < 0.001. This study concludes that improving teacher creativity can strengthen students’ learning motivation